Diplomasi Publik Baru dalam Penyajian Informasi dan Gambaran Budaya Jepang oleh Saluran Youtube ‘only in Japan’ - Putri Mentari Racharjo; R.M.T. Nurhasan Affandi (Universitas Padjadjaran, 2019)
The emergence of new media raises new forms of diplomacy, which one of them is the new public diplomacy. The emergence of new public diplomacy allows the public to be directly involved in the process of diplomacy. The practice of the new public diplomacy can be seen on Youtube, specifically on the ‘Only in Japan’ channel. This research is aimed to analyze the potrayal of Japanese culture on the Youtube channel